The women who spied for Britain female secret agents of the Second World War - Walker, Robyn (Amberley, 2014)
"Espionage is one of the world?s oldest professions, and it played an integral role in Allied successes and failures during the Second World War. Equal to men in both their bravery and in the sacrifices they made, the female undercover operatives of the Second World War deserve to have their incredible stories told. The Women Who Spied for Britain traces the fascinating and sometimes tragic stories of eight women who put their lives on the line and made invaluable contributions to the British war effort. Drawn from many different walks of life, including a princess, a beauty queen, a war widow, a teenage girl and a bawdy Australian journalist, all of these women shared a sense of adventure, daring and determination that allowed them to embrace the role of secret agent. Trained in the art of clandestine warfare, guerilla tactics and radio operation, these women worked closely with resistance movements throughout Occupied Europe. Their stories are portraits of courage, offering a mixture of thrilling adventure, gutsy humour, hard-fought triumphs and, for far too many, horrific tragedy." ... from publisher's website